Prediction Parameters of the Republican Budget for 2016 – 2018 and their Analysis - UTIBAYEVA, Gulzhan; UTIBAYEV, Begendyk; BAIDAKOV, Assilbek; ZHUSSUPOVA, Aigerim; SAPARBAYEV, Saule; ZHOLMUKHANOVA, Aigul; ZHUNUSOVA, Raushan (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
The article describes the prediction parameters of the republican budget for 2014 – 2016 in terms of the new economic policy of the state. Particular attention is paid to the formation of the revenue side of budgets, including due to the size of tax revenues, transfers, the amount of which is considered in dynamics. It also provides a comparative characteristic of the volume, structure and areas of budget crediting, and a comprehensive analysis and assessment of transactions with financial assets.